Violência contra a mulher : estudo de caso em uma instituição de ensino - Freitas, Mirna Cristina da Silva (2011)
The study research case with a quantitative approach and prospective data, carried out between December 2010 and February 2011 with the aim of identifying the profile of women in the study, to characterize the acts of violence in the type, frequency, location occurrence and aggressor, analyze the steps taken after the occurrence of acts of violence and the main consequences on the victims. The population consisted of 285 workers in a tertiary institution in Rio Grande do Norte. The results showed that 99 (34.74%) have between 51 to 60 years of age, 78 (27.37%) of 41 to 50 and 62 (21.75%) between 20 and 30 years, are considered color white, 162 (56.84%) have completed higher education, 171 (60.00%) and of these 97 (56.73%) reported having some post-graduate degrees, are married, 141 (49.47%) and have from zero to one child, 148 (51.93%) reside in the south of the city of Natal, 146 (51.23%) have a monthly income of three to five minimum wages, 171 (60.00%) and are mostly in the Technical Administrative Sciences 152 (53.33%), 77 (27.02%) reported having experienced violence, 60 (62.50%) episodes of verbal aggression, 26 (27.08%) of bullying , 05 (5.21%) of physical abuse and 05 (5.21%) sexual harassment; 05 (100.00%) assaults were made by the spouse or partner of the victims and co-workers is another profession were responsible for 18 (30.00%) verbal aggression, 15 (57.69%) bullying and 03 (60.00%) sexual harassment, 02 (40.00%) of victims of physical aggression and 18 (30.00 %) of verbal abused only once, 10 (38.46%) of bullying and 02 (40.00%) of sexual harassment experienced four or more times 05 (100.00%) assaults occurred at domestic and work stood out with 36 (60.00%), verbal abuse, 22 (84.62%), moral harassment and 04 (80.00%) sexual harassment, 35 (36.46%) told colleagues work and 31 (32.29%) for family and friends in 75 (78.13%) cases there was no intervention, 07 (7.29) were unable to respond if something had been done and 14 (14.58% ) have been reported intervention of these, 09 (64.29%) were taken by the heads of the victims, 26 (32.10%) did not notify the fact on the ground that no action would be taken, 62 (80.52%) felt stress , 5 (1.76%) of women turned away from work after the episode of violence, accounting for 198 days of absenteeism. It is concluded that there is a high rate of violence against women, even when they have a good socioeconomic status, and in this sense is important to establish bases of new proposals for improving control of cases of health professionals, especially nurses, to approach patients with a more investigative, and that by identifying a case of violence, be instructed about the paths to be followed for notification while providing psychological support to victims.